Western Experience in Strategic Planning for National Security - V. P. Nazarov (MGIMO University Press, 2019)
The purpose of this article is to provide an overview of the best Western practices in strategic planning with the view to improve the effectiveness of the Russian Federation national security policy in the face of new challenges and threats.Having analyzed Western approaches to ensuring national security, the article concludes that the political and governance practice needs to include more of strategic planning elements, such as strategic forecasting, monitoring, and national security assessment. Based on applicability to the Russian environment, the article particularly focuses on the American experience in strategic planning and discusses the origins and nature of the ideologeme of Americentrism that has dominated the American politics since 1990s. The author reveals how important role the use of soft power in specific national interests plays in the government policy for national security purposes and concludes that interrelation and mutual influence between planning and governance are indispensable.Having analyzed the Western practices, the article demonstrates the need to adjust significantly the strategic goal setting, first and foremost in Russia’s essential strategic planning documents.